2023
DOI: 10.1021/acs.est.3c00703
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Ultraviolet Treatment of Carbamazepine and NDMA in Water under 222 nm Irradiation

Abstract: Krypton chloride (KrCl*) excimer ultraviolet (UV) light may provide advantages for contaminant degradation compared to conventional low-pressure (LP) UV. Direct and indirect photolysis as well as UV/hydrogen peroxide-driven advanced oxidation (AOP) of two chemical contaminants were investigated in laboratory grade water (LGW) and treated secondary effluent (SE) for LPUV and filtered KrCl* excimer lamps emitting at 254 and 222 nm, respectively. Carbamazepine (CBZ) and N-nitrosodimethylamine (NDMA) were chosen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A separate experiment has been performed without a TiO 2 mesh electrode to see the effect of only UV light on the photolysis of H 2 O 2 for dye mineralization. Because of the low quantum yield of H 2 O 2 at 253 nm, 35 the degradation rate decreases, and results are shown in Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate experiment has been performed without a TiO 2 mesh electrode to see the effect of only UV light on the photolysis of H 2 O 2 for dye mineralization. Because of the low quantum yield of H 2 O 2 at 253 nm, 35 the degradation rate decreases, and results are shown in Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
“…Excimer UV lamps are nontoxic (mercury-free), have instantaneous startup time, and are easily scalable and repairable. Such excilamps are an efficient source for water disinfection, dye degradation, and micropollutant removal. ,, Murcia et al performed the photodegradation of different dyes using XeBr, KrCl, and Cl 2 excilamps and found that KrCl excilamps show the best removal percentage followed by XeBr and Cl 2 excilamps. In another study by the same research group, two excilamps were compared in a UV/H 2 O 2 process, and it concluded that excimer technology could be an excellent alternative to conventional methods .…”
Section: Introductionmentioning
confidence: 99%
“…To meet the above challenges, emerging UV light lamps are extensively investigated for UV-AOPs. One option was to adjust the emission wavelength of UV lamps to match the absorbance spectra of chemical reagents. For example, the UV lamps emitting at 280–300 nm were tested for chlorine photolysis, and medium-pressure mercury lamps (200–240 and 300–325 nm) or far-UV (222 nm) were studied to activate NO 3 – . , Another approach is the application of vacuum-UV (VUV, <200 nm) that can be absorbed by H 2 O to generate • OH in a chemical-free oxidation process. , In comparison to conventional UV/H 2 O 2 oxidation, VUV can be fully absorbed by H 2 O and significantly reduces the H 2 O 2 requirement. , One of 185 nm (VUV) is emitted by LPUV lamps designed with high-purity quartz as the wall. , These modified LPUV lamps emit dual wavelengths at 185 and 254 nm (VUV/UV), and are already frequently applied for the production of ultrapure water as well as the rapid measurement of total organic carbon …”
Section: Introductionmentioning
confidence: 99%
“…9 Excimer lamps (e.g., krypton chloride) emitting Far-UVC light at a peak emission wavelength at around 222 nm (UV 222 ) have emerged as promising alternatives to UV 254 for driving UV-AOPs. 20,21 Oxidant precursors (e.g., H 2 O 2 , 21 chlorine, 19 and nitrate 22 ) have been reported to have much higher molar absorption coefficients or quantum yields at 222 nm than 254 nm, 19 and give higher radical yields in the UV 222 -driven AOPs than the UV 254 -driven AOPs. PDS also has a 8.8-time higher molar absorption coefficient at 222 nm (146.9 M −1 cm −1 ) than at 254 nm (16.6 M −1 cm −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The UV/PDS AOP that has been reported in the literature, up to date, is largely driven by low-pressure mercury lamps with a peak emission wavelength at around 254 nm (UV 254 ). ,, However, the molar absorption coefficient of PDS at 254 nm is low (16.6 M –1 s –1 ), which gives low radical yields and demands more energy/light for micropollutant degradation by using the UV 254 /PDS AOP . Excimer lamps (e.g., krypton chloride) emitting Far-UVC light at a peak emission wavelength at around 222 nm (UV 222 ) have emerged as promising alternatives to UV 254 for driving UV-AOPs. , Oxidant precursors (e.g., H 2 O 2 , chlorine, and nitrate) have been reported to have much higher molar absorption coefficients or quantum yields at 222 nm than 254 nm, and give higher radical yields in the UV 222 -driven AOPs than the UV 254 -driven AOPs. PDS also has a 8.8-time higher molar absorption coefficient at 222 nm (146.9 M –1 cm –1 ) than at 254 nm (16.6 M –1 cm –1 ). , The quantum yield of PDS at 222 nm might also be higher than 254 nm because the photon energy at 222 nm (539 kJ einstein –1 ) is 1.14 times higher than at 254 nm (471 kJ einstein –1 ). , Thus, we hypothesized that the radical yields would be higher in the UV 222 /PDS AOP than the UV 254 /PDS AOP.…”
Section: Introductionmentioning
confidence: 99%